2006
DOI: 10.2147/vhrm.2006.2.3.213
|View full text |Cite
|
Sign up to set email alerts
|

Angiogenesis in cancer

Abstract: New growth in the vascular network is important since the proliferation, as well as metastatic spread, of cancer cells depends on an adequate supply of oxygen and nutrients and the removal of waste products. New blood and lymphatic vessels form through processes called angiogenesis and lymphangiogenesis, respectively. Angiogenesis is regulated by both activator and inhibitor molecules. More than a dozen different proteins have been identified as angiogenic activators and inhibitors. Levels of expression of ang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
766
0
14

Year Published

2015
2015
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 1,221 publications
(788 citation statements)
references
References 95 publications
8
766
0
14
Order By: Relevance
“…43,44 Hypoxiainducible factor 1 (HIF-1) controls oxygen delivery (via angiogenesis) to cancer tissues. 45,46 Our previous data using hif-1adPA mice showed that hif-1a over-expression in hepatocytes led to increased steatosis, while hif-1a deletion in hepatocytes protected mice from alcohol-induced liver injury.…”
Section: Discussionmentioning
confidence: 99%
“…43,44 Hypoxiainducible factor 1 (HIF-1) controls oxygen delivery (via angiogenesis) to cancer tissues. 45,46 Our previous data using hif-1adPA mice showed that hif-1a over-expression in hepatocytes led to increased steatosis, while hif-1a deletion in hepatocytes protected mice from alcohol-induced liver injury.…”
Section: Discussionmentioning
confidence: 99%
“…Further, the pro-angiogenesis activity of tumor cells becomes crucial for their survival in a microenvironment progressively more hypoxic, for a continuous supply of nutrients and oxygen [116]. The hypoxic TME triggers, also through oxidative stress −as shown in ovarian and prostate cancers [117][118][119], the tumor production of angiogenetic factors such as vascular-endothelial-growth-factor (VEGF), by upregulating hypoxia-inducible factor-1α (HIF-1α) [120]. Interestingly, HIF-1α is able to limit ROS accumulation in tumor cells, thus promoting cancer progression at later stages, by limiting the production of acetyl-CoA (the key molecule entering the TCA cycle) from glycolysis [121] and fattyacid oxidation [122].…”
Section: Mitochondrial Dynamics and Ros Production In Cancermentioning
confidence: 99%
“…These provide neoproliferation. Tumors may become necrotic without these substances, and hence sufficient vascular support is needed (7,8). These vascular networks, allowing the growth of benign tumors and the growth and metastasis of malignant tumors, can be blocked through various methods.…”
Section: Discussionmentioning
confidence: 99%